Germany - Kordel, Stefan; Weidinger, Tobias (10 Country Reports on Economic Impacts of TCNs (= Deliverable 4.3 of MATILDE project)., 2021)
This document presents a qualitative assessment of TCNs economic impact in the studied remote and rural regions of MATILDE countries – Austria, Bulgaria, Finland, Germany, Italy, Norway, Spain, Sweden, Turkey and in the United Kingdom – and in the framework of the foundational economy. Firstly, each report includes a description of the selected companies and the rationale for choosing them as well as the methodology and the ethical aspects related to the fieldwork and the context where they operate – building the knowledge of MATILDE regions produced under the previous tasks (WP2,3,4) and additional desk research and fieldwork gathered information. Secondly, each country report discusses, on the basis of the interviews and the literature, how migration has brought changes in the company/enterprise models, in particular whether there have been changes in the culture of doing business and promoting innovation (including social innovation). Thirdly, each national report discusses how migration has intertwined with the local community and territory, throughout the participation of migrants to local economy, focusing on how rurality and remoteness have played a role in the development of links or interaction with the local community and including also issues related to local welfare services. Moreover, those documents discuss the changes that migrants’ entrepreneurship have provoked and their perception by both the locals and the migrants’ themselves. Finally, they include a reflection on the policy related factors that are facilitating or hindering migrants’ entrepreneurship and innovation capacity.